The Influence of Digital Marketing and Service Quality on Customer Loyalty at Cafe Storyline in Palopo City - Utari, Afia; Aqsa, Muhammad; Dewintari, Putri (PT. EQUATOR SINAR AKADEMIA, 2026)
Digital marketing today This play a role important in introduce A products and reach customer in a way directly . Digital marketing techniques have the potential big in increase preference customer in buy something products , especially among​ child young people who tend to easy adapt with digital systems . Research This done in frame know influence digital marketing and quality service to loyalty Customers of Storyline Cafe in Palopo City . Research using primary data in the form of questionnaire to 100 respondents . Research results with analysis regression simple show influential digital marketing direct positive and significant to loyalty customers , but quality service No influential direct to loyalty . In No direct , digital marketing and quality service influential significant to loyalty through satisfaction customer .